Strategi Media Promosi Terhadap Pemasaran Produk Tabungan Haji DiBank Syariah - tria anggraini; Muhammad Iqbal Fasa (PT. Intelek Cendikiawan Nusantara, 2024)
This research aims to analyze the marketing strategy of the Hajj Savings product at Bank Muamalat and its effectiveness in enhancing competitive advantage. Using a qualitative approach, data were obtained through observation, interviews, and documentation. The results show that Bank Muamalat implements cooperation strategies with other institutions such as KBIH, as well as STP strategies (segmentation, targeting, positioning) and marketing mix (product, price, place, and promotion). Bank Muamalat focuses on price competition, exploring opportunities, and maintaining good relationships with customers. This research concludes that effective promotion can increase public interest in Hajj Savings products, thereby strengthening the bank's position in the Islamic banking market.